Kesulitan Peserta Didik dalam Menyelesaikan Soal Higher Order Thinking Skill (HOTS) Ditinjau dari Kemampuan Komunikasi Matematis - Musfira, Musfira; Badjeber, Rafiq; Nursupiamin (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
The purpose of this research is to identify the difficulties encountered by students in solving higher-order thinking Skill (HOTS) questions, considering their mathematical communication abilities. This research employs a descriptive method with a qualitative approach and a case study research design. The subjects of this study are 25 eighth-grade students from SMP Negeri 3 Palu. Three students were selected to represent the high, medium, and low categories of mathematical communication abilities, allowing for an analysis of their difficulties in solving HOTS questions. The research instruments include a mathematical communication ability test, a HOTS question test, and interview guidelines. Data analysis consists of data collection, data reduction, and conclusion. The study results indicate that students with high mathematical communication abilities experience difficulties in question C6, particularly in applying mathematical principles. Meanwhile, students with medium mathematical communication abilities need help in question C5, which involves the application of mathematical principles, as well as in question C6, where they struggle with applying concepts and solving verbal problems. On the other hand, students with low mathematical communication abilities encounter difficulties in questions C4 and C6, which require the application of mathematical concepts and principles and solving verbal problems. Developing students' critical thinking skills and mathematical literacy can mitigate these difficulties. Students can better grasp mathematical concepts by applying analysis and evaluation in critical thinking. Additionally, engaging in interpretation within mathematical literacy can enhance their ability to solve verbal problems more effectively.